The Effectiveness of the Problem Based Learning Model Assisted by Snake and Ladder Game Media on Student Learning Outcomes - Widiyastuti Widiyastuti; Mahluddin Mahluddin; Arif Wiratama (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the effect of implementing the Problem-Based Learning (PBL) model assisted by the Snake and Ladder Game (SLG) media on the cognitive learning outcomes of students in Mathematics in grade II at MI Al-Munawwarah, Jambi City. This study used a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. There were 57 students in the study, divided into an experimental class and a control class. The experimental class was taught using the PBL model assisted by the SLG media, while the control class used the PBL model without the game media. Data collection was conducted through pre-tests and post-tests, while data analysis used descriptive and inferential statistics, including normality tests, homogeneity tests, Independent Sample t-Tests, and N-Gain analysis. The results showed that the average post-test scores and N-Gain of the experimental class were higher than those of the control class. The t-test results obtained a significance value of 0.047 (< 0.05), which indicates a significant difference in learning outcomes. Thus, it can be concluded that the application of the PBL model assisted by the Snake and Ladder Game media has a significant effect on improving students' cognitive learning outcomes in mathematics learning.